Analysis of the conformational properties of amine ligands at the gold/water interface with QM, MM and QM/MM simulations - Liang, Dongyue; Hong, Jiewei; Fang, Dong; Bennett, Joseph; Mason, Sara E.; Hamers, Robert J.; Cui, Qiang (Royal Society of Chemistry, 2017)
We describe a strategy of integrating quantum mechanical (QM), hybrid quantum mechanical/molecular mechanical (QM/MM) and MM simulations to analyze the physical properties of a solid/water interface. This protocol involves using a correlated ab initio (CCSD(T)) method to first calibrate Density Functional Theory (DFT) as the QM approach, which is then used in QM/MM simulations to compute relevant free energy quantities at the solid/water interface using a mean-field approximation of Yang et al. that decouples QM and MM thermal fluctuations; gas-phase QM/MM and periodic DFT calculations are used to determine the proper QM size in the QM/MM simulations. Finally, the QM/MM free energy results are compared with those obtained from MM simulations to directly calibrate the force field model for the solid/water interface. This protocol is illustrated by examining the orientations of an alkyl amine ligand at the gold/water interface, since the ligand conformation is expected to impact the chemical properties (e.g., charge) of the solid surface. DFT/MM and MM simulations using the INTERFACE force field lead to consistent results, suggesting that the effective gold/ligand interactions can be adequately described by a van der Waals model, while electrostatic and induction effects are largely quenched by solvation. The observed differences among periodic DFT, QM/MM and MM simulations, nevertheless, suggest that explicitly including electronic polarization and potentially charge transfer in the MM model can be important to the quantitative accuracy. The strategy of integrating multiple computational methods to cross-validate each other for complex interfaces is applicable to many problems that involve both inorganic/metallic and organic/biomolecular components, such as functionalized nanoparticles.
Keywords: UMBC High Performance Computing Facility (HPCF)